Caste in Kerala - Panikkar, K.N. (ed.) (Delhi : Primus Books, 2020)
The essays in this volume deal with caste reform movements in Kerala of the nineteenth and twentieth centuries, which form the most significant development in the history of caste in modern times. The core of this book caste in Kerala consists of four essays on cast reform movements among the namputhiris, nairs, ezhavas and Dalits. They are prefaced by two essays which discuss the origin of the caste system in Kerala and the historical process of its fragmentation and proliferation. The closing essay throws light on the role caste plays in contemporary politics. Over time, most of the external attributes of caste system have been rendered irrelevant by the changes that have occurred in society with the decline of the feudal order and the subsequent movements for caste reform. Yet, caste has persisted. An analysis of the internal contradictions within these movements throws light on the enigma that caste continues to be.
Keywords: Social problems; Politics and government; Social conditions